The Concept of Uchitel / Uchenik (Teacher / Pupil): Motivating Signs - M. G. Iurchenko (Kemerovo State University, 2021)
The research was based on fifteen etymological and explanatory dictionaries of the Russian language and featured the motivating signs of the macroconcept uchitel / uchenik (teacher / pupil). Conceptual, descriptive, and interpretive analyses revealed 46 motivating signs, which indicates the long history of the macroconcept. The signs constituted thirteen blocks: 1. Results of cognitive activity (expertise, knowledge, skills, views, and experience). 2. The process and result of learning (teach, instruct, hold classes, inculcate, enrich, acquire, preach, train, study, memorize, learn). 3. Methods of teaching (instruction, teaching). 4. Method of memorization (repeat, get used to, get used, be adjusted to). 5. Participants of the educational process (teacher, student, lecturer, learner, mentor, educator), head of teaching, cleric, novice). 6. Mode of behavior (custom) 7. Commitment (admirer, fan, follower). 8. Violent ways of teaching (beat, punish, force). 9. Science (science, scientist, learning). 10. Educational institutions (school, college). 11. Effort (try). 12. Trust (trust). 13. Learning activity (learning, learning activity, studies, curricular, lesson, schooling, textbook). The signs grew less numerous with time: the contemporary Russian linguistic worldview contains only 41 out of the original 46.